Refleksi Implementasi Jaminan Kesehatan Nasional pada Pelayanan Kedokteran Gigi di Fasilitas Kesehatan Tingkat Pertama Kota Tangerang Tahun 2017 - Indra Rachmad Dharmawan (Center for Health Policy and Management, 2017)
This study aims to find out how the reflection of the implementation of national health insurance (JKN) in dentistry services at first-rate health facilities (FKTP) Tangerang City in 2017. The condition of awareness of Indonesian people for oral health is still not good, thus requiring process improvement, and The concept of better service. Such improvements can be implemented in the form of dental services in FKTP. This research uses qualitative method that aims to know the implementation of dental services in health insurance, in accordance with the rules, conditions and regulations that apply. The research was conducted in FKTP of Tangerang City Health Office, 15 Puskesmas and 15 pratama clinics in collaboration with BPJS health. The results showed the presence of dentists in each FKTP has been fulfilled as well as the condition of dental infrastructure facilities is sufficient. In terms of utilization of dentistry services, JKN participants in Puskesmas are very low. There are still differences in the number of JKN participants in each FKTP. Dentistry services in JKN are still many kinds of service in serving JKN participants, the highest number of dental disease cases in the community in JKN not all can be served in primary service so there are still many references.